Negative refraction in all-dielectric metamaterial - Han, Yuetao (Nanyang Technological University, 2020)
This project focuses on the use of all dielectric resonators to achieve metamaterial negative refraction. Most of the previous literatures and methods discussed in them are based on metals, however, such designs can cause strong wear and tear on the performance of devices. In this paper, Mathematica software is used to calculate the effective permeability and permittivity of the cylindrical dielectric resonator. Then, the Comsol simulation software is used to prove that negative permeability and negative permittivity can be realized simultaneously in the periodic arranged array of dielectric resonator structure in a specific frequency range.